Acute posterior multifocal placoid pigment epitheliopathy in a child. Case report - Jan Studnicka; A. Stepanov,; E. Rencova,; Ya. Breznajova; M. Burova; H. Langrova; P. Rozsival (Oftalʹmologiâ)
To present our findings and the course of acute posterior multifocal placoid pigment epitheliopathy (APMPPE) with macular edema in a child.